PREPARATION OF FUTURE TEACHERS FOR THE DEVELOPMENT OF GIFTEDNESS OF PRESCHOOL AND PRIMARY SCHOOL CHILDREN BY MEANS OF DRAMATIZATION - Demchenko, Olena; Stakhova, Inna; Davydova, Maryna; Larina, Iryna; Lymar, Yulia; Strilets, Svitlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The necessity and main directions of preparation of future teachers for work with gifted children of preschool and primary school age are shown. The author's definition and structure of readiness of future educators to work with gifted children are presented. The signs of giftedness are analyzed and the characteristics of different types of giftedness are presented. The importance of identifying talented individuals in an educational institution and creating a developmental environment for the development of their abilities and creative self-realization is substantiated. The importance of theatrical activity for the development of general and special abilities, creativity, talent and the formation of non-cognitive qualities of preschool and primary school children is shown. The results of diagnostics of awareness of future teachers with the theoretical and methodological principles of using theatrical activities as a means of developing children's talents are presented. The main directions of training future teachers in the educational process of higher education institutions, aimed at mastering students' special knowledge, development of professional qualities, skills and abilities necessary for the use of dramatization in working with different categories of potentially gifted children.